2017
DOI: 10.3389/fpls.2017.00717
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Polyphenoloxidase, Peroxidase, and β-Glucosidase in Phenolics Accumulation in Olea europaea L. Fruits under Different Water Regimes

Abstract: Olive fruits and oils contain an array of compounds that contribute to their sensory and nutritional properties. Phenolic compounds in virgin oil and olive-derived products have been proven to be highly beneficial for human health, eliciting increasing attention from the food industry and consumers. Although phenolic compounds in olive fruit and oil have been extensively investigated, allowing the identification of the main classes of metabolites and their accumulation patterns, knowledge of the molecular and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 69 publications
7
37
0
Order By: Relevance
“…Finally, higher expression levels of the olive GLU gene were detected under water deficit conditions in Picual and Arbequina cultivars, mainly at turning stage. Similar results have been recently reported for the OeGLU12-like2 gene from cultivar Frantoio ( Cirilli et al, 2017 ). The increase in the olive GLU transcript level detected under water deficit conditions, with the corresponding increase in the enzyme activity, could also significantly contribute to explain the higher content of secoiridoid derivatives reported in VOO obtained from olive fruit under water stress conditions ( Artajo et al, 2006 ; Stefanoudaki et al, 2009 ).…”
Section: Discussionsupporting
confidence: 91%
“…Finally, higher expression levels of the olive GLU gene were detected under water deficit conditions in Picual and Arbequina cultivars, mainly at turning stage. Similar results have been recently reported for the OeGLU12-like2 gene from cultivar Frantoio ( Cirilli et al, 2017 ). The increase in the olive GLU transcript level detected under water deficit conditions, with the corresponding increase in the enzyme activity, could also significantly contribute to explain the higher content of secoiridoid derivatives reported in VOO obtained from olive fruit under water stress conditions ( Artajo et al, 2006 ; Stefanoudaki et al, 2009 ).…”
Section: Discussionsupporting
confidence: 91%
“…The overall higher phenolic content found in fruits and oils from Ubeda could be related with the lower rainfall of this location and similarly, the lower phenolic content of genotypes grown in Cordoba could be explained by its highest rainfall. The increase of phenolic content in VOO with reduced water availability has been well documented for olive (Marra et al, 2016 ; Cirilli et al, 2017 ) although this relation has not always been clearly observed (Pierantozzi et al, 2014 ). However, taking into account that the three environments differs on many aspects (soil type, temperature regime, rainfall, etc.…”
Section: Discussionmentioning
confidence: 89%
“…The metabolism of phenolic compounds in the olive tree is very complex, and is modulated by genetic (Talhaoui et al, 2016 ) and environmental factors (Romero and Motilva, 2010 ) that determine the final phenolic composition of olive fruits. In a similar way, the influence of agricultural practices such as limited irrigation (Cirilli et al, 2017 ), optimization of pruning to increase light availability (Proietti et al, 2012 ) or selection of optimum harvest date (Famiani et al, 2000 ) have also been described. The phenolic glycosides present in the olive fruit are later transformed and modified by endogenous hydrolytic and oxidative enzymes that are activated during the oil extraction process.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, treatment with UV-B radiation did not show any effects [52]. Additionally, reduced PPO activities after UV-C treatments were observed in other vegetable crops [53,54].…”
Section: Variety and Year O Cultivationmentioning
confidence: 81%